Ischemic Stroke Risk After Acute Coronary Syndrome. Issue 7 (July 2016) - Yaghi, Shadi; Pilot, Markeith; Song, Christopher; Blum, Christina A.; Yakhkind, Aleksandra; Silver, Brian; Furie, Karen L.; Elkind, Mitchell S. V.; Sherzai, Dean; Sherzai, Ayesha Z.
Abstract : Background: Prior studies show an increased risk of ischemic stroke (IS) after myocardial infarction; however, there is limited evidence on long‐term risk and whether it is directly related to cardiac injury. We hypothesized that the risk of IS after acute coronary syndrome is significantly higher if there is evidence of cardiac injury, such as ST‐segment elevation myocardial infarction (STEMI) or non‐STEMI, than when there is no evidence of cardiac injury, such as in unstable angina. Methods and Results: Administrative claims data were obtained from all emergency department encounters and hospitalizations at California's nonfederal acute care hospitals between 2008 and 2011. Patients with STEMI, non‐STEMI, and unstable angina were identified using appropriate International Classification of Diseases, Ninth Revision, Clinical Modification codes. The primary outcome was IS during 2 years of follow‐up. Unadjusted and adjusted Cox proportional hazards models were used to determine the association between acute coronary syndrome subtype and IS risk. We identified 73 059 patients with a diagnosis of STEMI (n=26 427), non‐STEMI (n=39 833), or unstable angina (n=6819) during the study period. In the fully adjusted models that included potential confounders such as atrial fibrillation and congestive heart failure, the risk of IS was higher with STEMI (hazard ratio 4.17, 95% CI 3.00–5.83; P <0.001) and non‐STEMI (hazard ratio 3.73, 95% CI 2.68–5.19, P <0.001) compared with unstable angina. Conclusions: Non‐STEMI and STEMI confer an equally increased risk of IS. Studies exploring IS mechanisms in cardiac patients are needed to improve and tailor stroke prevention strategies.